Quantum Dot Devices - Wang, Zhiming M.; Wang, Zhiming M. (Lecture Notes in Nanoscale Science and Technology,, 2012)
Quantum dots as nanomaterials have been extensively investigated in the past several decades from growth to characterization to applications. As the basis of future developments in the field, this book collects a series of state-of-the-art chapters on the current status of quantum dot devices and how these devices take advantage of quantum features. Written by 56 leading experts from 14 countries, the chapters cover numerous quantum dot applications, including lasers, LEDs, detectors, amplifiers, switches, transistors, and solar cells. Quantum Dot Devices is appropriate for researchers of all levels of experience with an interest in epitaxial and/or colloidal quantum dots. It  provides the beginner with the necessary overview of this exciting field and those more experienced with a comprehensive reference source.   Covers the current status and future trends in  research on quantum dot devices Features contributions from leading experts in each pplications area Suitable for experienced researchers as well as those new to the field.